Test Results of WADGPS System using Satellite-based Ionospheric Delay Model for Improving Positioning Accuracy - So, Hyoungmin; Jang, Jaegyu; Lee, Kihoon; Song, Kiwon; Park, Junpyo (Journal of Positioning, Navigation, and Timing, 2016)
Most existing studies on the wide-area differential global positioning system (WADGPS) employed a grid ionosphere model for error correction in the ionospheric delay. The present study discusses the application of satellite-based ionospheric delay model that provides an error model as a plane function with regard to individual satellites in order to improve accuracy in the WADGPS. The satellite-based ionospheric delay model was developed by Stanford University in the USA. In the present study, the algorithm in the model is applied to the WADGPS system and experimental results using measurements in the Korean Peninsula are presented. Around 1 m horizontal accuracy was exhibited in the existing planar fit grid model but when the satellite-based model was applied, correction performance within 1 m was verified. KCI Citation Count: 1